INCLUSIVE EDUCATION: A SYSTEMATIC REVIEW OF THE IMPACT AND EFFICACY OF SOFT SKILLS DEVELOPMENT FOR STUDENTS WITH DISABILITIES - Nur Maslina Mastam; Rozniza Zaharudin, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The significance of enhancing the soft skills of students with disabilities is investigated in this essay, with a particular emphasis on enhancing their academic, personal, and professional achievements. It seeks to equip individuals with the necessary skills to prepare them for a more inclusive and fair future. This is through addressing challenges such as a lack of interpersonal skills, such as communication, cooperation, and flexibility. Here, the research employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach, conducting a systematic review by scouring academic databases and journals for pertinent articles published within the last three years. In addition, the systematic search employed academic databases like Scopus and Web of Science (WoS). After rigorous searching, the final dataset comprised (n = 25) studies. There are three identities: 1) Social interaction and skill development for students with disabilities; 2) employment-related soft skills for students with disabilities; and 3) a variety of approaches to support students with disabilities. Furthermore, the study highlights the need to incorporate targeted interventions into educational curricula and expresses support for inclusive policies that place an emphasis on the overall development of students. Cultivating a culture that prioritises empathy, understanding, and skill development while also actively working to remove barriers and foster an inclusive atmosphere holds the potential for society to contribute significantly to the academic as well as professional success of students with disabilities.